PENGUATAN KETERAMPILAN GABUNGAN KELOMPOK TANI (GAPOKTAN) DALAM PENANGANAN KORBAN GIGITAN ULAR DI WILAYAH PERTANIAN KECAMATAN PANTI, KABUPATEN JEMBER - Haristiani, Ruris; Yunanto, Rismawan Adi; Setioputro, Baskoro; Rokhani; Al Muvidah, Nadira Rifqi; Ni'mah, Afa Faiqotun (Universitas Mataram, 2024)
Indonesia, as one of the world's largest tropical countries, has a very high incidence of snake bites. Among agricultural workers, the high risk of snake bites is attributed to the lack of necessary preventive measures, such as wearing gloves, boots, and other personal protective equipment to avoid snake bites. Open living spaces in rural areas and the habit of sleeping on the floor also pose a potential risk of bites from nocturnal snakes. Therefore, this community service aims to innovate interventions and explore the outcomes of intervention innovations regarding the management of first aid for snake bites in the community. The applied method involves providing education on first aid for snake bites to the community through lectures and demonstrations. There was an improvement in the knowledge level, with the category of